Determinants of Purchasing and Loyalty of European Guests Choosing Green Hotel - Yuniati, Nining (E-Journal of Tourism; Volume 7 Number 2 (September 2020)DO - 10.24922/eot.v7i2.60995, 2020)
It is very important to pay attention to what is considered in consumer purchasing decisions. European visitors are guests who are quite dominant as green hotel users in Yogyakarta. This study seeks to examine a model of purchasing behavior and loyalty of visitors from Europe. By examining a sample of 215 hotel guests, it was found that from the five variables that were indicated to influence the decision to choose green hotel i.e. experience, environmental concern, image, price, and reference group, it turns out that price does not have a significant effect. This means that segments that have a high environmental concern tend to prioritize factors beyond price. European visitors can then be referred to as green consumers who have characteristics including hassle-free segments, easy to manage, and less complained. This study also examines the relationship model between Purchasing, Satisfaction, and Loyalty on green consumers, where satisfaction is an important element in fostering customer loyalty. Keywords: green consumers, green hotel, purchasing behavior